Bahan Ajar Maharah Qiro’ah berbasis Aktifitas I’rob di Prodi Pendidikan Bahasa Arab UNISMA - Junaidi, Mohammad Rifqi; Syarif, Syihabuddin; Idris, Mohammad; Naftali, Siti Rihana (Lugawiyyat, 2024)
This research aims to develop effective maharah qira'ah teaching materials based on i'rob activities. This approach is expected to improve students' understanding and ability to analyze Arabic sentence structures, especially in the context of qira'ah. The method used in this research is research and development (RD) by adopting the Sugiyono model. Data was collected through interviews, observation and documentation studies, then analyzed using qualitative descriptive techniques. The research results show that the i'rob activity-based teaching materials developed can help students understand and apply i'rob rules in reading Arabic texts. The activities designed involve exercises in understanding sentence context, identifying i'rob elements, as well as application exercises in reading texts. Thus, it is hoped that the development of teaching materials can improve the quality of maharah qira'ah learning and facilitate students in mastering reading skills well.